Does sex really matter? Explaining intraspecies variation in ocean acidification responses. (28th February 2017) - Ellis, Robert P.; Davison, William; Queirós, Ana M.; Kroeker, Kristy J.; Calosi, Piero; Dupont, Sam; Spicer, John I.; Wilson, Rod W.; Widdicombe, Steve; Urbina, Mauricio A.
Abstract : Ocean acidification (OA) poses a major threat to marine ecosystems globally, having significant ecological and economic importance. The number and complexity of experiments examining the effects of OA has substantially increased over the past decade, in an attempt to address multi-stressor interactions and long-term responses in an increasing range of aquatic organisms. However, differences in the response of males and females to elevated p CO2 have been investigated in fewer than 4% of studies to date, often being precluded by the difficulty of determining sex non-destructively, particularly in early life stages. Here we highlight that sex can significantly impact organism responses to OA, differentially affecting physiology, reproduction, biochemistry and ultimately survival. What is more, these impacts do not always conform to ecological theory based on differential resource allocation towards reproduction, which would predict females to be more sensitive to OA owing to the higher production cost of eggs compared with sperm. Therefore, non-sex-specific studies may overlook subtle but ecologically significant differences in the responses of males and females to OA, with consequences for forecasting the fate of natural populations in a near-future ocean.